2011
DOI: 10.1111/j.1365-2923.2010.03904.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of evaluation in longitudinal versus traditional clerkships

Abstract: Preceptors and students perceived evaluation in an LIC more favourably than evaluation on block clerkships. For educators working to improve student evaluation, further examination of the LIC structure and evaluation processes that seem to enhance both formative assessment and summative evaluation may be useful to improve the quality of evaluation and feedback.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 21 publications
5
46
0
1
Order By: Relevance
“…Longitudinal integrated clerkships may be one model enabling earlier identification of failing students. 23 Similar to previous research, our cohort of failing students included more men than women. 6 We found that a greater percentage of male than female students had deficiencies in the professionalism domain and in critical deficiencies related to conduct, though we found no statistically significant relationship between gender and critical deficiencies in professionalism or conduct.…”
Section: Discussionsupporting
confidence: 57%
“…Longitudinal integrated clerkships may be one model enabling earlier identification of failing students. 23 Similar to previous research, our cohort of failing students included more men than women. 6 We found that a greater percentage of male than female students had deficiencies in the professionalism domain and in critical deficiencies related to conduct, though we found no statistically significant relationship between gender and critical deficiencies in professionalism or conduct.…”
Section: Discussionsupporting
confidence: 57%
“…In the context of WBA, these techniques might translate to longitudinal relationships between learners and assessors. A few studies suggest that assessments by people who know a learner well are perceived to be more fair, honest and accurate than those by people who have brief or infrequent interactions with the learner . Such relationships may be hard to come by in our current ‘rotational approach’ to clinical training .…”
Section: Continuity Relationshipsmentioning
confidence: 99%
“…Changing the structure of clinical learning can enhance both learning and the usefulness of feedback synergistically. An ongoing working relationship between a trainee and a supervisor allows feedback to become part of the dialogue of shared work, rather than a message delivered after the fact, such as when a faculty member completes a written evaluation that leads the learner to ask: ‘Why didn’t he tell me that while we were working together?’ An ongoing relationship enhances trust between individuals, and trust that the feedback shared in that context represents relevant, valid information for learning 10 . Longitudinal relationships allow feedback to serve the forward‐looking goal of improving performance within that context, and can enhance the supervisor’s comfort in delivering feedback within an ongoing relationship.…”
mentioning
confidence: 99%